2020
DOI: 10.3389/fonc.2020.01072
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Air-Way Fluid in Lung Cancer. Detection of Periostin in Bronchoalveolar Lavage (BAL)

Abstract: Background: Bronchoalveolar lavage (BAL) is a specific type of airway fluid. It is a commonly used clinical specimen for the diagnosis of benign diseases and cancers of the lung. Although previous studies have identified several disease-associated proteins in the BAL, the potential utility of BAL in lung cancer is still not well-studied. Based upon the fact that the majority of secreted proteins are glycoproteins, we have profiled N-glycoproteins in BAL collected from lung cancers, and investigated the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…The MS-based quantitative N-glycoproteomic technique was also used to analyze BALF samples, revealing periostin in all samples from lung cancer patients. Validation of the screened periostin with ELISA in another 39 BALF samples also yielded the same conclusion 65 .…”
Section: Application Of Balf In the Diagnosis And Prognosis Of Lung C...mentioning
confidence: 55%
“…The MS-based quantitative N-glycoproteomic technique was also used to analyze BALF samples, revealing periostin in all samples from lung cancer patients. Validation of the screened periostin with ELISA in another 39 BALF samples also yielded the same conclusion 65 .…”
Section: Application Of Balf In the Diagnosis And Prognosis Of Lung C...mentioning
confidence: 55%
“…Recent studies have shown that elevated levels of POSTN were detected in the serum of patients with different types of malignancies, indicating that it would be an effective diagnostic and prognostic biomarker 34 . It was also demonstrated that POSTN could be detected in bronchoalveolar lavage of patients with lung cancer, and the POSTN level in the bronchoalveolar lavage was significantly higher than that in benign lung disease 35 . In this study, our results demonstrated that the level of serum POSTN was upregulated in patients with lung cancer‐related MPE compared to patients with BPE, which is consistent with previous studies by Xu et al21 and Zhang et al 22 Their studies indicated that serum POSTN levels were significantly increased in patients with NSCLC when compared to patients with benign lung diseases and healthy controls, and high levels of serum POSTN were associated with poor prognosis of patients with NSCLC.…”
Section: Discussionmentioning
confidence: 98%
“…A clinical trial conducted by Nakamura et al (UMIN000012339) demonstrated that periostin and squamous cell carcinoma antigen were highly expressed during the pathogenesis of acute bronchitis caused by respiratory syncytial virus (RSV), and they were associated with the subsequent development of asthma. In a recent study, proteomic analysis, and ELISA assay of periostin in BAL fluid of lung cancer patients showed increasing periostin levels in all subtypes of lung cancer (67).…”
Section: Lung Cancermentioning
confidence: 91%
“…Lung cancer patients BALF Proteomic analysis and ELISA assay of BALF showed increasing in periostin expression in all subtypes of lung cancers (67). with eosinophilic asthma and persistent airflow limitation (37).…”
Section: Cell Culture Mediummentioning
confidence: 99%